Peer Educator Community Partnership Program Women's Reproductive Rights Through the Rumah Pd Community (Early Marriage) in Gunung Sari Singosari Village Malang - yuliani, ita; Sondakh, Jenny JS; Ardhini, Innas Tiara (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
Early marriage has an impact related to reproductive rights, namely: the risk of death due to pregnancy, childbirth and postpartum (Cipto and Awatiful, 2014), but many people (women) with early marriage do not understand their reproductive rights (Cipto and Awatiful, 2014). The knowledge of the prospective Peer Educators before receiving the training was found that half had less knowledge about women's reproductive rights and almost half had sufficient knowledge about chocolate brownies. The knowledge of the Peer Educator candidates after receiving the training obtained that all of them are knowledgeable about women's reproductive rights and all have good knowledge about chocolate brownies. All prospective Peer Educators graduated and were appointed as Peer Educators for women's reproductive rights and the manufacture of steamed chocolate brownies. Volunteers' knowledge prior to receiving counseling from Peer Educators was almost entirely less knowledgeable about women's reproductive rights and almost half had sufficient knowledge about chocolate brownies. The knowledge of the volunteers after receiving counseling from Peer Educator was mostly good knowledge about women's reproductive rights and almost all had good knowledge about chocolate brownies. Mother After receiving training, the peer educator has increased knowledge and the peer educator is able to pass on to the volunteers about women's reproductive rights and the making of steamed chocolate brownies.The results of the Wilcoxon signed ranks test with = 0.05 obtained a p value of 0.025 which is smaller than = 0.05 which means Ha is accepted. Therefore, there is an effect of training / counseling on reproductive knowledge and making steamed chocolate brownies